Endotoxin-induced cytokine, chemokine and white blood cell profiles of variable stress-responding sheep. (2nd November 2021) - Naylor, D.; Sharma, A.; Li, Z.; Monteith, G.; Mallard, B. A.; Bergeron, R.; Baes, C.; Karrow, N. A.
Abstract: Individual variation of the hypothalamic-pituitary-adrenal (HPA) axis response to stress could contribute to variable stress resiliency of livestock. During stress events, the innate immune system can also become activated and work in concert with the neuroendocrine system to restore homeostasis, while minimizing tissue damage. The purpose of this study was to assess immune function in variable stress-responding sheep in response to bacterial lipopolysaccharide (LPS) endotoxin immune-challenge. High (HSR, n  = 12), middle (MSR, n  = 12), and low-stress responders (LSR, n  = 12) were selected from a population of 112 female lambs and classified based on serum cortisol concentration after receiving an intravenous bolus of LPS (400 ng/kg). Blood was collected from the jugular vein at 0 and 4 hrs post-LPS challenge to monitor changes in serum pro- and anti-inflammatory cytokines and chemokines, and white blood cell populations. Rectal temperature was recorded hourly to monitor fever. HSR had the greatest increase in rectal temperature and strongest pro-inflammatory IL-6 and IFN-γ cytokine responses compared to MSR and LSR. HSR and MSR had stronger anti-inflammatory IL-10 cytokine and CCL2 chemokine responses than LSR. White blood cell counts changed between 0 and 4 h; however, no differences were detected among the variable stress response groups. The distinct inflammatory response in variable stress responding sheep could contribute to individual differences in stress resiliency and this warrants investigation in the context of other types of stress. LAY SUMMARY: Acute inflammation was studied in sheep stress-phenotyped using bacterial lipopolysaccharide. Sheep selected based on stress responsiveness (i.e. serum cortisol concentration) have different immune responses to bacterial stress. Specifically, high-stress responders have a more pronounced inflammatory response than low-stress responders.